KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 28 PADANG - Rahman, Abdul; Basri, Irfani; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is as follows. First, describe reading skills in understanding the exposition text of class VIII students of SMP Negeri 28 Padang. Second, describe the writing skills of exposition text of grade VIII students of SMP Negeri 28 Padang. Third, analyze the correlation of reading skills understanding exposition text and exposition text writing skills of class VIII students of SMP Negeri 28 Padang. This type of research is quantitative research with descriptive methods. Research design is correlational research. The sample of this study amounted to 40 people. The sampling technique in this study was simple random sampling. The instruments used in this study are objective tests for reading skills in understanding exposition text and performance tests for text writing skills exposition. Data were analyzed by percentage formula, formula for calculating average, normality test, homogeneity test, and t-test. The results of this study are the following three things. First, the reading skills of understanding the exposition text of class VIII students of SMP Negeri 28 Padang were of good quality, with an average score of 77.64. Secondly, the writing skills of exposition text of grade VIII students of Padang Public Middle School 28 are more than qualified, with an average value of 73.38 below the KKM (75). Third, there is a positive and significant relationship between reading skills understanding exposition text and exposition text writing skills of class VIII students of SMP Negeri 28 Padang at a significant level of 0.05 and degrees of freedom (dk) = n-1 because t count> ttable is 6.70> 1, 68. Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman Teks Eksposisi, Keterampilan Menulis Teks Eksposisi